Over the counter use of topical corticosteroid for skin conditions among patients before attending skin specialist clinic in Nepal: A qualitative study. - Yogesh Poudyal; Nishika Aryal; Anuja Rajbhandari; Mukti Ghimire; Sanjaya Acharya; Shristi Raut; Bishal Joshi; Sunil Pokharel; Phaik Yeong Cheah; Bipin Adhikari (PLOS Global Public Health)
Access to topical corticosteroids (TCs) globally includes over the counter (OTC) sale without proper guidelines, exacerbating treatment-resistant infections and complicating outcome of skin conditions. The main aim of the study was to evaluate the reasons behind OTC use of TCs among patients with skin conditions before attending a skin specialist clinic. This study was conducted from September 2021 to March 2022. The study included in-depth interviews (IDIs) and observations, among a total of thirty-one patients with specific skin conditions using TCs, at the Sarnath Skin Centre in Siddhartha Nagar (Bhairahawa), Nepal. All interviews were conducted in the Nepali language, audio-recorded, transcribed and translated into English and were coded and analyzed in NVivo. Among the 31 individuals diagnosed with Dermatophytosis, Melasma, Eczema, common treatments included use of Sonaderm (Clobetasol, Gentamycin and Miconazole), Derma-KT (Clobetasol, Gentamicin, Ketoconazole and Iodochlorhydroxyquinoline) and steroid-infused products from non-medical sources for prolonged periods of time, exposing patients to transient recovery and perpetuating a vicious cycle of OTC treatment seeking until patients failed to recover. OTC seeking was facilitated by participants' easy access to drug dispensers, suggestions from and practice of family and friends which often led to temporary relief for a few weeks/months. In addition, access factors (e.g., distance, cost, time), convenience factors (e.g., ease of presenting at the drug store compared to skin clinic) also influenced the choice for OTC. There was a lack of knowledge related to adverse effects of topical steroids, including proper guidance on the use of topical medications and limitations of home remedies. OTC use of topical medications poses significant challenges, often leading to complicated skin cases that present late at skin-specialist clinics. A multi-pronged public and community engagement approach is critical to curb the treatment seeking dynamics among patients developing skin conditions.